2011
DOI: 10.1063/1.3529441
|View full text |Cite
|
Sign up to set email alerts
|

Mirrorlike pulsed laser deposited tungsten thin film

Abstract: Mirrorlike tungsten thin films on stainless steel substrate deposited via pulsed laser deposition technique in vacuum (10(-5) Torr) is reported, which may find direct application as first mirror in fusion devices. The crystal structure of tungsten film is analyzed using x-ray diffraction pattern, surface morphology of the tungsten films is studied with scanning electron microscope and atomic force microscope. The film composition is identified using energy dispersive x-ray. The specular and diffuse reflectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Deuterium retention in these conditions is much more efficient than in experiments where hydrogen saturation was studied by exposing the AMA mirror to the gas phase or electrolytic solution. From the measured dependence of the absorbed deuterium mass on the ion fluence (up to 1.5·10 25 ion/m 2 ) it was possible to estimate the efficiency of deuterium absorption to be ~10% for an ion energy of ~60 eV. This is about ten times higher than in the electrolytic hydrogenation experiments [38].…”
Section: Fig (8)mentioning
confidence: 86%
See 2 more Smart Citations
“…Deuterium retention in these conditions is much more efficient than in experiments where hydrogen saturation was studied by exposing the AMA mirror to the gas phase or electrolytic solution. From the measured dependence of the absorbed deuterium mass on the ion fluence (up to 1.5·10 25 ion/m 2 ) it was possible to estimate the efficiency of deuterium absorption to be ~10% for an ion energy of ~60 eV. This is about ten times higher than in the electrolytic hydrogenation experiments [38].…”
Section: Fig (8)mentioning
confidence: 86%
“…The Basel group operates with Rh films (and to some extent also Mo films) produced by magnetron sputtering and has a typical thickness ~2 μm (e.g., [23]). The two other groups study the behavior of films obtained by a pulsed laser deposition technique in vacuum [24,25]. All main publications connected with investigation of film mirrors were recently enumerated in a short review [26].…”
Section: Film Mirrorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. The tight focusing of the high power laser beam onto the target was avoided as it leads to the formation of liquid droplet which develops microstructures and craters onto the film surface (Mostako et al 2011). The micrograph of single shot laser spot onto the photographic paper is shown in the Fig.…”
Section: Methodsmentioning
confidence: 99%
“…9 Pulsed laser deposition (PLD) is another simple technique for the deposition of high quality crystalline thin film of various oxides and heavy metals. [13][14][15][16] In the present note growth of epitaxial ruby thin film on sapphire substrate is presented via PLD. The deposited film was subjected to temperature dependent photoluminescence (PL) studies and shown to act as linear temperature sensor in low temperature range.…”
mentioning
confidence: 99%